Syzygium Aromaticum Alleviates Cerium Chloride-Induced Neurotoxic Effect In The Adult Mice. (2nd January 2019) - Kadri, Yamina; Nciri, Riadh; Bardaa, Sana; Brahmi, Noura; Saber, Saidi; Harrath, Abdel Halim; Aldahmash, Waleed; Alwasel, Saleh; Mohany, Mohamed; El Feki, Abdelfatteh; Salah Allagui, Mohamed
Abstract: Previous studies have brought to light the toxic effect of cerium chloride (CeCl3 ) but very little is known about the oxidative brain injury caused by this metal. Medical plants have a well-recognized role in the management of damage caused by pollutants such as CeCl3 . Syzygium aromaticum, a potent natural source of bioactive compounds and rich in secondary metabolites, has a broad range of biological functions. The aim of this study is to investigate the capacity of Syzygium aromaticum ethanol extract (ESA) to improve the adverse effects of CeCl3 in the brain tissue. Adult mice were exposed to CeCl3 (20 mg/kg body weight [BW]), with or without ESA, for 60 days. We investigate mice's behavior, damages of cholinergic system and oxidative stress parameters in mice brain. In the present study, i n vitro test confirmed that ESA has antioxidant capacity attributed to the presence of flavonoids, polyphenols, and tannins contents. In vivo study showed that CeCl3 caused brain injuries manifested in memory impairment, increase in acetylcholinesterase activity, oxidative stress biomarkers (lipid, proteins, enzymatic and non-enzymatic antioxidant systems), and histopathological alteration in brain tissue. Addition of ESA repaired memory impairment, decreased acetylcholinesterase activity, restored oxidative state, and prevented histopathological alteration. In conclusion, the experimental results showed the protective effects of ethanol extract of Syzygium aromaticum against cerium-induced brain damage.